Acute renal failure in children under two years of age - Fahmi Ahmed, Nariman (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Acute renal failure (ARF) in children is a catastrophic, life -threatening eventAim of the study: the aim of the present study is to find out the etiology and outcome of patients with acute renal failure below two years of age admitted to the hospital.Patients and methods: A prospective study was carried out on children below 2 years of age (with exclusion of neonatal period) presented with acute renal shut downadmitted to Children Welfare Teaching Hospital during the period from Jan. 1st, 2007tojan30th,2008.Results: the study group included 100 patients with acute renal failure, 69 males and 31 females with M/F ratio 2.2:1.Age range was between (2 months - 2 years).Prerenal ARF was the commonest type seen in 67(67%) patients and hypovolemia due to (gastrointestinal loss) was the prominent etiology it was found in 53(53%)cases. ARF due to renal and post-renal causes found in 21(21%) and 12(12%) cases respectively, six (6%) patients only presented with non-Oligouria. Forty four patients (44%) required peritoneal dialysis, while(56)patients improved on conservative management only and most of them (53 %) were the pre-renal group. Ninety two (92%) patients had either complete or partial recovery of their renal function, eight (8%) patients died from ARF.Conclusion: prerenal ARF particularly hypovolemia secondary to gastrointestinal loss was the most common causative group of ARF in our patients, with goodprognosis for the recovery of renal function in most patients. To evaluate and validate markers of acute kidney injury more prospective clinical studies required.